Investigating composing strategies in the writings of Arab postgraduate students’ project papers - Nor Fariza Mohd Nor,; Tan, Kim Hua; Noraini Ibrahim, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
Students at higher education are frequently required to write essays and project paper. In fact, writing is very much integral to the students’ learning experience in higher education. Writing essays trains students into the expectations of the discipline, and how to present their thoughts and reflection to their lecturers. Research into students’ writing at university has shown that the experience of writing not only helps students to become familiar with the standards and style of written expression expected in their disciplines, but it also helps them to clarify their understanding of the subject matter about which they are writing. This study examines the written work of five postgraduate students from the Middle East. The data collection procedures involved analysis of the students’ written work and interviews. The present study used several taxanomies of ESL writing strategies in order to investigate and understand the students’ conceptualization of their writing tasks. The findings revealed that the students employed several composing writing strategies in order to help them work with, think about and manipulate the materials required in order to do the writing task. The writing process was also interactive, which means that the students used and build upon their previous knowledge, skills and strategies in writing. The present study ends with the suggestion that students’ attention must be directed to the foundations of writing a project paper in order that they have a greater sense of audience’s awareness, in addition to increasing their knowledge on discourse conventions of academic writing.